Strengthening Tertiary Students Writing Skills Through T.R.E.N.D. Model - Pek, Lim Seong; Mee, Rita Wong Mee; Shing, Soo Ruey; Theesmas, Daeshela; Nadarajan, Na-Thinamalar Magiswary (Asian Journal of Contemporary Education, 2019)
Writing has always been subjected as a difficult task for students taking English language subjects during their first two semesters studying in tertiary education. For these students, writing a composition has been a task they would prefer to avoid doing. One of many reasons is the inability to first generate and organize their ideas for writing tasks. Besides, they faced difficulty in expressing themselves fluently or being able to write sentences that are grammatically correct in the target language. Realizing the importance of writing skills among undergraduates in the tertiary education, a study was carried out on 200 undergraduates who attended a day Malaysian University English Test (MUET) workshop to examine students’ writing ability through a proposed model of Transferring, Restructuring, Engaging, Negotiating and Documenting (T.R.E.N.D.). The findings had shown significant improvement in learners’ writing in term of coherency and the development of ideas after the workshop. As a whole, the use of T.R.E.N.D. Model had helped to improve students’ writing ability in terms of not only language proficiency, but also their level of confidence.